Pharmacognostical standardization and in vitro pediculocidal activity of Datura innoxia and Cyclea peltata - ,Sridhar D1, Vinod K.R1, David B1, Sandhya S1*, Prathyusha V1, Govardhan S2 (Current Botany, 2011)
Datura innoxia and Cyclea peltata are two medicinally important plants with multiple medicinal values. The folklore of India uses these two plants for pediculocidal activity. Hence we have initiated to standardize both the plant parts pharmacognostically and then evaluate its pediculocidal potency. The micro anatomical studies of seeds of D.innoxia and leaves of C.peltata were studied. The proximate analysis, fluorescence analysis, preliminary chemical tests were performed for the both plant parts. Fixed oils were isolated from seeds of D.innoxia and the GC-MS studies were performed. The selected crude extract of C.peltata and the fixed oil of D.innoxia were evaluated for pediculocidal activity by filter paper diffusion bioassay. Permethrin(1%) was used as the standard and water as control. Lignified sclerenchyma was identified as tissue of diagnostic importance for D.innoxia seed and lignified unicellular covering trichomes was found to be the most important tissue of diagnostic importance for the leaves of C.peltata. Both the plants showed the presence of alkaloids as one of the major chemical constituents. GC-MS report of fixed oils from D.innoxia revealed the presence of different types of fatty acids. Both the plants showed potent pediculocidal activity. Among the two plants Datura innoxia seed oil was found to be best. It showed almost same activity as that of standard drug used. Further investigations have to be carried out on the isolated compounds which can set a base for the development of lead compounds with potent pediculocidal activity.